PROPUESTA DE SEÑALÉTICA PARA EL FOMENTO DEL TURISMO EN EL “BOSQUE PROTECTOR RUMI WILCO” DE LA PARROQUIA DE VILCABAMBA, CANTÓN LOJA. - Piedra Apolo, Renato Antonio (2016)
This thesis revolves around the theme "Paths and signage for tourist promotion of Bosque Protector Rumi Wilco" aimed at conservation and protection of natural, through the implementation of trails and signage, theme today has aroused great interest worldwide, allowing green areas are protected to safeguard resources. The Rumi Wilco Protected Forest is located to the south west of the province of Loja, 40 km from the provincial capital Vilcabamba parish, magical corner of Southern Ecuador is located, with a population of 118,532 inhabitants and a climate of 22 degrees Celsius average. This place is known worldwide as "Valley of Longevity". Its geographic location is a biodiverse area of incomparable beauty. Rumi Wilco Protected Forest is an environmental area and has the potential to become a promising site for conducting trails, this has been raised by this research work where you have to know the basic guidelines for adapting and implementing the trails of signage and infrastructure that encourage visitors to gather and contribute to tourism development for the Reserve. In order to develop the theme raised general objectives: Design a proposal of trails and interpretive signage and information to facilitate access to visitors, who can enjoy and appreciate the different natural attractions of the intervention sites, and three specific. To meet the overall objective the following specific objectives were raised. The first specific objective was to develop an inventory to characterize the natural attractions of the protected forest Rumi Wilco, the second was to design the tourist signs for the trails with its own budget for the protected forest, the third objective of the project Socialize authorities Vilcabamba parish and representatives of tourist agencies and environmental management of Rumi Wilco. For all objectives different methods and techniques that enabled a study to identify each were used. The methods of the Ministry of Tourism (Mintur), in which detailed information is summarized chips used for the inventory of attractions. The description of the attraction was done, the same as classified according to: category, type, subtype. In this phase, which is attractive to investigate their relevant characteristics and proceeds to the hierarchy consisting of the individual analysis of each appeal is tentatively selected. In addition to the capacity of mathematical and scientific methods it was used and the processing is visited each of the paths to see what state each so you can replace the data in formulas methods of Miguel Cifuentes . To detail the trails, designs and signs gathering information with GPS, Geographic Information Systems (SLG) with this a trail map and signage was developed and for the realization of the signs is based on the methodology of the Ministry held Tourism (Mintur), since you have to keep the same standardization and is adapted according to the different 5 characteristics suitable to the area. The designs of the trails were conducted with Adobe Illustrator and Adobe Photoshop program. To carry out the budget was made, collection costs proformas making signs, construction of infrastructure, which was chosen the most suitable. Upon completion of the research stages it was obtained as a final result the proposed trails and interpretive and informative signage, to facilitate access for visitors to enjoy and appreciate the different natural attractions of sites that exist in the reserve, improving the image and the services of the same, to help disseminate and promote tourism in this place of great importance. As for the results it was possible to develop an inventory of attractions Protected Forest Rumi Wilco, tourism carrying capacity it was determined, and finally, the proposed signs designs and technical and administrative budget was made. In the proposal and signage materials to be used and the budget, the need to invest to run with the amount of US $ 7,014.72 detailing. In this budget the costs for signage, promotion, detailed trail. With the implementation of the proposal aims to boost tourism and sustainable development strategy, avoiding cause negative impacts to biological components of the Reserve and also the signaling is to better serve visitors with signs location messages and activities that can make the time and allowed to interact better capturing their attention and optimizing their knowledge with detailed site information that are walking. Finally awareness campaign by the Ministry of Tourism and Ministry of Environment, aimed at communities thus help preserve the natural attractions that promote eco-tourism, both domestic and foreign environment; and entities seeking funding for project implementation, relating to domestic and foreign'S NGOs or government organizations that are interested in conservation and environmental protection, also make agreements with universities to promote further research; and determine and protect natural sites helping to boost tourism development in our country.